Pendidikan Karakter pada Pembelajaran Bahasa Indonesia - Wati Fatmawati (Indonesian Journal of Applied Linguistics Review, 2017)
This research is to gain a comprehensive understanding about character education in Indonesian language learning process of eleventh grade science students in SMA Islam Al- Azhar Kelapa Gading Jakarta. The goal is elaborated in four subfocus, namely (1) character education stated in the syllabus, (2) implementation of character education in learning process, (3) the role of teachers and learners in character education, and (4) learning evaluation system character education in Indonesian language. This study used qualitative method with ethnography methods. From this study, it is concluded that character education in Indonesia language learning in SMA Islam Al-Azhar Kelapa Gading Jakarta is a blend of the curriculum 2013 with the curriculum of character education developed by the school, and is divided into four pillars: rabbaniyyah, insaniyyah, ilmiyyah, and alamiyyah. These four pillars are integrated into a complete and ongoing learning activities so that the Islamic character instilled on students is expected to be inherent in them and applied in everyday life.